Effects of light-emitting diode spectral combinations on growth and quality of pea sprouts under long photoperiod - Zhang, Siqi; Guo, Xiaolei; Li, Junyan; Zhang, Yinghua; Yang, Youming; Zheng, Wengang; Xue, Xuzhang (Frontiers in Plant Science, 2022)
Pea sprouts have rich nutrition and are considered good for heart health. In this study, the kaspa peas and black-eyed peas were chosen to clarify effect of different LED spectral combinations on growth, yield and nutritional quality of pea sprouts under long photoperiod(22h light/2h dark). The results showed that the two pea varieties responded differently to light spectral combinations. Black-eyed pea sprouts had higher plant height, fresh weight per plant, dry weight per plant, soluble sugar content and lower malondialdehyde (MDA) content than kaspa peas under the same light treatment. Compared with white light, red:blue ratio of 2:1 significantly increased peroxidase (POD) and superoxide dismutase (SOD) activity, soluble sugar and soluble protein content of kaspa pea sprouts, and decreased MDA content of black-eyed pea sprouts. Blue light was negatively correlated with plant height of pea sprouts, and positively correlated with SOD activity, vitamin C, soluble sugar and soluble protein content. Antioxidant capacity, yield and nutritional quality of black-eyed pea sprouts were higher than those of kaspa pea sprouts under the same light treatment. Blue light improved the nutritional quality of pea sprouts. Compared with other lgiht treatments, the red-blue ratio of 2:1 was more conducive to improving the antioxidant capacity and nutritional quality of pea sprouts under long photoperiod.